Relationship between Serum Uric Acid Levels and Severity of Hypertension in Adult Patients - Maqsood, Saeed; Shah, Sadullah; Khan, Radhia; Samiullah, Samiullah; Shah, Naimat Ullah; Ullah, Farman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertension is a major cardiovascular risk factor worldwide, and hyperuricemia has been implicated as both a marker and a potential contributor to increased blood pressure. Understanding the relationship between serum uric acid levels and hypertension severity may aid in risk stratification and management. Objective: To evaluate the association between serum uric acid levels and the severity of hypertension in adult patients. Methods: A retrospective observational study was conducted at a tertiary care institution from March 2023 to August 2023. Adult patients (≥18 years) diagnosed with hypertension were included. Demographic data, comorbidities, blood pressure readings, and serum uric acid levels were extracted from medical records. Hypertension was classified as mild, moderate, or severe according to established guidelines. Statistical analysis included mean ± SD, frequencies, percentages, and correlation analysis between uric acid levels and blood pressure. A p-value <0.05 was considered statistically significant. Results: A total of 120 patients were analyzed, with a mean age of 52.6 ± 11.2 years. Serum uric acid levels increased significantly with hypertension severity, with mean levels of 5.8 ± 1.2 mg/dL in mild, 6.7 ± 1.4 mg/dL in moderate, and 7.9 ± 1.5 mg/dL in severe hypertension (p < 0.001). A positive correlation was observed between serum uric acid and both systolic and diastolic blood pressure. The findings were consistent across age and sex subgroups, suggesting an independent association. Conclusion: Serum uric acid levels were positively associated with the severity of hypertension in adult patients. Monitoring and managing uric acid may provide a valuable tool for risk stratification and optimizing hypertension care.